2015
DOI: 10.11564/29-1-718
|View full text |Cite
|
Sign up to set email alerts
|

Application of mHealth to improve service delivery and health outcomes: Opportunities and challenges

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 36 publications
0
17
0
2
Order By: Relevance
“…However, despite the hopes that mHealth can improve access and quality of health care while simultaneously reducing cost, little is yet known whether it can actually achieve these goals in practice (Barlow et al, 2007;Free et al, 2013;Shahrokni et al, 2015;Vesel, Hipgrave, Dowden, & Kariuki, 2015). Reasons for that concern include a tendency of technology designers to focus on usability of interventions rather than actual health outcomes; a lack of standardized, replicable study designs; and an absence of frameworks for evaluation (Labrique, Vasudevan, Kochi, Fabricant, & Mehl, 2013;Vesel et al, 2015). Furthermore, Vesel et al (2015) stated that it is essential to address issues of technology acceptance to ensure successful implementation of mHealth programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the hopes that mHealth can improve access and quality of health care while simultaneously reducing cost, little is yet known whether it can actually achieve these goals in practice (Barlow et al, 2007;Free et al, 2013;Shahrokni et al, 2015;Vesel, Hipgrave, Dowden, & Kariuki, 2015). Reasons for that concern include a tendency of technology designers to focus on usability of interventions rather than actual health outcomes; a lack of standardized, replicable study designs; and an absence of frameworks for evaluation (Labrique, Vasudevan, Kochi, Fabricant, & Mehl, 2013;Vesel et al, 2015). Furthermore, Vesel et al (2015) stated that it is essential to address issues of technology acceptance to ensure successful implementation of mHealth programs.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for that concern include a tendency of technology designers to focus on usability of interventions rather than actual health outcomes; a lack of standardized, replicable study designs; and an absence of frameworks for evaluation (Labrique, Vasudevan, Kochi, Fabricant, & Mehl, 2013;Vesel et al, 2015). Furthermore, Vesel et al (2015) stated that it is essential to address issues of technology acceptance to ensure successful implementation of mHealth programs.…”
Section: Introductionmentioning
confidence: 99%
“…mHealth, ‘the use of mobile technologies for health related activities’, is rapidly expanding throughout the world (Vesel et al 2015:1684). Service provision and management of complex conditions, such as non-communicable diseases (Opoku, Stephani & Quentin 2017) and palliative care (Allsop, Namisango & Powell 2018), benefited from mHealth applications in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Service provision and management of complex conditions, such as non-communicable diseases (Opoku, Stephani & Quentin 2017) and palliative care (Allsop, Namisango & Powell 2018), benefited from mHealth applications in Africa. Mobile phone applications or mHealth applications have the advantage of reaching large populations in different geographical areas across gender and social divides (Vesel et al 2015). It connects users to services that were previously unavailable to them or were only available through substantial effort in terms of travel, expenses and waiting times (Abaza & Marschollek 2017; Opoku et al 2017; Vesel et al 2015; Watkins et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies related to MHealth in the field of safety, research conducted by Larissa Jennings et al showed that only 7 out of 173 articles met the inclusion criteria. In general, MHealth is currently used in aspects related to HIV/AIDS, sexual and reproductive health, health-based microenterprise, non-communicable diseases, support emergency medical services, online help-seeking, maternal and child healthcare, medical and health education, service delivery and health outcomes [9]- [15]. Therefore, MHealth function needs to be expanded because MHealth interventions delivered through Text Messaging (TM) has the potential to improve healthy life style behaviors in adolescents, such as increasing physical activity.…”
Section: Introductionmentioning
confidence: 99%